3x+4(-3)=0

Simple and best practice solution for 3x+4(-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+4(-3)=0 equation:


Simplifying
3x + 4(-3) = 0

Multiply 4 * -3
3x + -12 = 0

Reorder the terms:
-12 + 3x = 0

Solving
-12 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 3x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 3x = 0 + 12
3x = 0 + 12

Combine like terms: 0 + 12 = 12
3x = 12

Divide each side by '3'.
x = 4

Simplifying
x = 4

See similar equations:

| 3(x-4)+7=4x+5 | | 8x-37=2x+35 | | 6(y+38)-19=43 | | 3x+32=2x+26 | | 5(3x+2y)= | | 15025=45.5t^2+6100 | | -36-6x=7x+2x | | 10n^2-6=994 | | 5(7x+5)whenx=10solve | | 85=(x)(4x-3) | | 10n^2=994 | | N^2+9n+15=7 | | (x+5)+(2x+15)+(2x+10)=90 | | 5(2x-2)=3x+11 | | x(4x+13)=-3 | | x+(X*.10)=1280418 | | 5x+2x^2+2=0 | | h(t)=-4.9t^2+32+2 | | 4x-15+3x=5+7x-19 | | -4p+11-(-5p)-2= | | 36x^2-36x-216=0 | | 400+50x=4000 | | -81=-4+7(6b-5) | | y+4=0.5x+1 | | -7y+12+2y-1= | | 6(x+3)-8x=36 | | 4(8k+5)= | | (3x-5)(2x+8)= | | (x+3)(x+3)=X^2+81 | | 456=(20+2x)(15+2x) | | 1+4(x-8)=4-5(x-1) | | x^2+y^2-6x+4y+6=0 |

Equations solver categories